Acceleration‐based sliding mode hierarchical control algorithm for shake table tests. (14th August 2021) - Yao, Hongcan; Tan, Ping; Yang, T. Y.; Zhou, Fulin
Abstract: Existing control algorithms for seismic shake table tests (STTs) generally exhibit limitations such as poor acceleration tracking for displacement control, instability that results in table drift for direct acceleration, force, or velocity control, and the lack of a theoretical justification for hybrid control. Therefore, a reliable control algorithm has become key for effective shake table control. This paper presents acceleration‐based sliding mode control (SMC) as a solution to the drawbacks of the traditional force‐based SMC; in this manner, the influence of the force of the tested structure applied on the table as well as unmodeled complex nonlinear forces, such as friction, are counteracted. An acceleration‐based sliding mode hierarchical control (ASMHC) algorithm is proposed, where the acceleration‐based SMC is used as the high‐level controller to generate the corrected acceleration command, and the low‐level controller, that includes feed‐forward and feedback control, tracks the acceleration command in real time. The high‐level controller, having zero asymptotic stability, and the low‐level controller, designed based on the system transfer function, ensure tracking stability in time and frequency domains, respectively. The proposed ASMHC algorithm was first verified by a series of bare STTs, and was then applied to a real STT of a two‐story steel structure. The experimental results show that the proposed ASMHC algorithm can achieve good tracking of displacement, velocity, and acceleration in both time and frequency domains, which ensures accurate reproduction of seismic excitation in STTs.